Master nerd e kpopper : maneiras de estar-junto - Rodrigues, Adriele Cristina (2019)
There is a growth of a geeky and / or kpopper audience, reflected in blockbuster blockbuster movies about Korean superheroes, Korean record-breaking bands, and even the consumption of items considered retro. To understand this scenario, this research aims to study the reasons that group youths in an event focused on kpoppers and nerds such as the Master Nerd, 2018 held in Cuiabá/MT on June 9 and 10. Specific objectives mirror the ways of conceptualizing terms; accompany young people at the event, register and describe the event, interview organizers and participants; analyze interviews in order to respond to the overall objective. Therefore, we adopt a methodological approach that involves ethnography, netnography, questionnaire and interview, in order to understand the ways of being together with nerds and kpoppers in the event.